EFEKTIVITAS PENGGUNAAN MEDIA KOMIK STRIP TERHADAP HASIL BELAJAR SISWA PELAJARAN SEJARAH SMA MUHAMMADIYAH 1 PONTIANAK - Raswin Ramjas; Husni Syahrudin; Andang Firmansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis investigation plans to decide the adequacy of utilizing funny cartoon media on understudy learning results in history class X IIS 1 SMA Muhammadiyah 1 Pontianak. This investigation utilizes a Quasi Experimental technique with the plan of "Nonequevalent Control Group". The populace in this examination were all understudies of class X IIS SMA Muhammadiyah 1 Pontianak and the example of this investigation were understudies of class X IIS 1 SMA Muhammadiyah 1 Pontianak, adding up to 32 individuals. The information assortment instruments in this investigation were talk with sheets, perception sheets, and test sheets through composing questions, legitimacy and dependability. The consequences of information investigation showed that the pretest mean score of the control class was 51.56, the trial class was 53.43 and the post-test normal score of the control class was 68 and the trial class was 77.35. In view of the aftereffects of the estimation of the Hypothesis (Test - t), it is realized that the worth of t check (5.04)> t table (2.00) then, at that point Ha is acknowledged and Ho is dismissed. This implies that there is the adequacy of understudy learning results between the control class who were dealt with utilizing traditional techniques and the exploratory class understudies, to be specific X IIS 1 who were treated by applying Comic Media. It very well may be inferred that the adequacy of funny cartoon media has been effectively applied in further developing the set of experiences learning results of class X IIS 1 SMA MuhammadiyahKeywords: Comic Media, Effectiveness, Learning Outcomes, History Subjects